Wczesnośredniowieczne groty strzał z poroża i kości - Mitelsztet, Szymon (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2023)
The text aims to draw attention to the issue of early medieval antler and bone arrowheads, rarely discussed in historiography. Tracing the history of research and bringing closer the opinions of individual researchers shows how the interpretations of these monuments in archaeological literature have changed over the years. The text discusses and characterizes the findings of arrowheads from the territory ruled by the Piast Dynasty together with an attempt to divide them into types according to the typology of A. F. Medvedev for finds from the territory of ancient Rus. These issues are only an introduction to further research in this field.